2016
DOI: 10.1177/0731684416669248
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of tensile properties of epoxy resin by using micro-fiber specimens

Abstract: In unidirectional carbon fiber-reinforced plastic laminates, the distance between fibers can varies from submicron to micron length scales. The mechanical properties of the matrix at this length scale are not well understood. In this study, processing methods have been developed to produce high quality epoxy micro-fibers with diameters ranging from 100 to 150 µm that are used for tensile testing. Five types of epoxy resin systems ranging from standard DGEBA to high-crosslink TGDDM and TGMAP epoxy systems have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Nor can defects explain the colossal ductility (plastic deformation and failure strain) seen in our experiments with epoxy fibers. Only scarce evidence exists in the literature for similar (and milder) size effects in epoxy fibers [13,16] but largely without explanation. We attempt to partly deal with this issue below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nor can defects explain the colossal ductility (plastic deformation and failure strain) seen in our experiments with epoxy fibers. Only scarce evidence exists in the literature for similar (and milder) size effects in epoxy fibers [13,16] but largely without explanation. We attempt to partly deal with this issue below.…”
Section: Resultsmentioning
confidence: 99%
“…These authors also reported, without further discussion, the observation of a highly ductile behavior of their epoxy fibers. Recently Misumi et al [16] studied the tensile behavior of fibers made of five different types of epoxies and compared the mechanical properties (yield stress, failure stress, failure strain, modulus and toughness) of fiber and bulk materials. Here too the epoxy fibers showed ductile behavior with a distinct yield point in all resin systems, whereas the macroscopic specimens exhibited brittle behavior with no yield point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, for the complete curing of partially cured glassy polymers in their curing mode, a thermal postcuring stage is included. The curing mode (temperature and time) was typically selected empirically (see, e.g., the experimental sections of papers [ 5,6 ] ), and this process might consist of several stages. For example, DiFrancia et al [ 5 ] cured samples in three stages: (a) 1 hr at 150°C; (b) 1 hr at 210°C and; (c) 2 hr at 230°C.…”
Section: Introductionmentioning
confidence: 99%
“…In ref. [6], the samples were successively cured at 80°C for 1 hr, 130°C for 30 min, and 180°C for 2 hr; in some cases, the epoxy resin was cured for 1 hr at 130°C, and then for 2 hr at 180°C. Such an approach does not guarantee complete curing.…”
Section: Introductionmentioning
confidence: 99%